Improving forehand performance through functional core training - Genevois, Cyril (ITF Coaching & Sport Science Review, 2015)
This article highlights the importance of functional core strengthening to improve forehand performance. It suggests on-court physical training exercises aimed at improving core rotation power and vertical stability of the body.